Weak stability transition region near the orbit of the Moon. Issue Volume 15:Issue S364(2019) (October 2021) - Makó, Zoltán; Salamon, Júlia
Abstract: This paper provides a study on the weak stability transition region in the framework of the planar elliptic restricted three-body problem. We define the lower boundary curve of the weak stability transition region and as a particular case, we determine this curve in the Sun-Earth system. The orbit of the Moon is near the lower boundary of the weak stability transition region.